2008
DOI: 10.1111/j.1582-4934.2007.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐cell cross‐talk between mesenchymal stem cells and cardiomyocytes in co‐culture

Abstract: The goals of the study were: (1) to explore the communication between human mesenchymal stem cells (MSC) and rat cardiac myocytes resulting in differentiation of the stem cells and, (2) to evaluate the role of mitochondria in it. Light and fluorescence microscopy as well as scanning electron microscopy revealed that after co-cultivation, cells formed intercellular contacts and transient exchange with cytosolic elements could be observed. The transport of cytosolic entity had no specific direction. Noticeably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 34 publications
8
169
0
1
Order By: Relevance
“…Alternatively, we showed that the transport of mitochondria was from MMSCs to neurons or glial cells. Such mitochondrial transfer between MMSCs and cardiomyocytes or renal epithelial cells was previously reported by us [14,16], and others [15,48,49]. Moreover, it has been shown that such a mitochondria "donation" can result in recovery of lost mitochondrial functions in recipient cells [50].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Alternatively, we showed that the transport of mitochondria was from MMSCs to neurons or glial cells. Such mitochondrial transfer between MMSCs and cardiomyocytes or renal epithelial cells was previously reported by us [14,16], and others [15,48,49]. Moreover, it has been shown that such a mitochondria "donation" can result in recovery of lost mitochondrial functions in recipient cells [50].…”
Section: Discussionmentioning
confidence: 73%
“…Because we previously demonstrated that cocultivation of MMSCs with cardiac cells or epitheliocytes associates with proper differentiation [14,16], we explored the possibility of directed differentiation of MMSCs toward neurons or astrocytes after cocultivation. However, after 24 hours of cocultivation of MMSCs with neural culture, we could not detect the expression of neurospecific b-III-tubulin (supplemental online Fig.…”
Section: Cocultivation Of Mmscs With Neuronal Culture Did Not Inducementioning
confidence: 99%
See 1 more Smart Citation
“…In previous works studying the direct contact interaction between heterogonous cell types, cell types after coculture were sorted by either labeling cell types with cell tracker dyes [49,50] or using specific surface antigens [13]. Our preliminary test indicates that these separation methods might yield a small false positive or false negative rate in the separated cell populations, and in the downstream, might affect the mRNA profiling such as secreting factors and differentiation markers, in which the expression levels might be highly varied.…”
Section: Discussionmentioning
confidence: 99%
“…Besides electrical signals, bacteria, HIV and quantum dot can be transported by MNTs between mesenchymal stem/stromal cells (MSCs) or immune cells [10,16,24,25], and in our study, mitochondria and intercellular vesicles could be transported via MNTs between CMs and FBs ( Figure 5) [5]. ATP and motor protein kinesin and dynein are required for the cargo transfer [10,26,27].…”
Section: Transport Of Organelles and Signalsmentioning
confidence: 99%